16 Effectiveness of a health promotion stand at a UK university to raise awareness on obesity-related weight bias and stigma: a pilot study. (12th April 2022) - Naseer, Fathimath; Baird, Judith; Price, Ruth; Douglas, Pauline; Livingstone, Barbara
Abstract : Nutrition Innovation Centre for Food and Health (NICHE), Ulster University, UK Introduction: Weight bias leads to the stigmatisation of individuals with obesity and has been associated with exacerbating psychological and physiological stress as well as further weight gain. 1 2 As such, there is a need for interventions to effectively address weight bias and stigma-reduction. 3 Aim: The aim of this observational study was to evaluate the understanding of obesity-related weight bias and stigma amongst university students and staff. Method: A health promotion stand was set up in Ulster University on World Obesity Day 2020. Students and staff who engaged were presented with definitions of weight bias and stigma, associated consequences and the importance of person-first-language. Subsequently they were asked to translate the new knowledge into practical suggestions or advice to help combat weight bias/stigma. They were also given the option to sign a pledge to ameliorate weight bias/stigma. All suggestions were categorised into common sub-groups as shown in table 1 . Results: 101 students and staff pledged their support and 83 gave a suggestion to minimise weight bias/stigma. In the latter group, the majority (71%) had a sound understanding of weight bias and stigma. However, 24 participants (29%) appeared to have confused the body acceptance initiative with reducing weight bias and stigma ( table 1 ). This was further verified through their interaction and comments with the volunteers at the stall. Conclusion: This pilot evaluation provides empirical evidence that 'minimising weight bias/stigma' and the 'body acceptance initiative' may be easily confused and even addressed interchangeably. Education initiatives to distinguish between these concepts is warranted to reduce weight-related stigma and improve access to care for individuals with obesity. References: Pearl R. Weight bias and stigma: public health implications and structural solutions. Social Issues and Policy Review 2018;12 (1):146–182. doi https://doi.org/10.1111/sipr.12043 Stewart S, Ogden J. The role of BMI group on the impact of weight bias versus body positivity terminology on behavioral intentions and beliefs: an experimental study. Frontiers in Psychology 2019;10. doi: https://doi.org/10.3389/fpsyg.2019.00634 World Health Organisation, 2017, Weight bias and obesity stigma: considerations for the WHO European Region, World Health Organisation (2017), viewed on 12 March 2020, http://www.euro.who.int/en/health-topics/noncommunicable-diseases/obesity/publications/2017/weight-bias-and-obesity-stigma-considerations-for-the-who-european-region-2017